Comparative genomic analysis of 5Mg chromosome of Aegilops geniculata and 5Uu chromosome of Aegilops umbellulata reveal genic diversity in the tertiary gene pool - Yadav, Inderjit S.; Rawat, Nidhi; Chhuneja, Parveen; Kaur, Satinder; Uauy, Christobal; Lazo, Gerard; Gu, Yong Q.; Doležel, Jaroslav; Tiwari, Vijay K. (Frontiers in Plant Science, 2023)
Wheat is one of the most important cereal crops for global food security. Due to its narrow genetic base, modern bread wheat cultivars face challenges from increasing abiotic and biotic stresses. Since genetic improvement is the most sustainable approach, finding novel genes and alleles is critical for enhancing the genetic diversity of wheat. The tertiary gene pool of wheat is considered a gold mine for genetic diversity as novel genes and alleles can be identified and transferred to wheat cultivars. Aegilops geniculata and Ae. umbellulata are the key members of the tertiary gene pool for wheat and harbor important genes against abiotic and biotic stresses. Homoeologous-group five chromosomes (5Uu and 5Mg) have been extensively studied from Ae. geniculata and Ae. umbellulata as they harbor several important genes including Lr57, Lr76, Yr40, Yr70, Sr53 and chromosomal pairing loci. In the present study, using chromosome DNA sequencing and RNAseq datasets, we performed comparative analysis to study homoeologous gene evolution in 5Mg, 5Uu, and group 5 wheat chromosomes. Our findings highlight the diversity of transcription factors and resistance genes, resulting from the differential expansion of the gene families. Both the chromosomes were found to be enriched with the “response to stimulus” category of genes providing resistance against biotic and abiotic stress. Phylogenetic study positioned the M genome closer to the D genome, with higher proximity to the A genome than the B genome. Over 4000 genes were impacted by SNPs on 5D, with 4-5% of those genes displaying non-disruptive variations that affect gene function.